Factors influencing purchase intention towards counterfeit products among selected Malaysian consumers in Kuala Lumpur / Sharmimi Shuhada Che Mohd Nizam - Che Mohd Nizam, Sharmimi Shuhada (Faculty of Business and Management, 2019)
The purpose for this study is to investigate the factors influencing selected Malaysian to purchase counterfeit products. To add, this study has comprised three independent variables which are brand image, price and social influence while the dependent variable is purchase intention towards counterfeit products. This study focuses on selected Malaysians in Kuala Lumpur. 384 questionnaires were distributed to the respondents around Kuala Lumpur. In addition, this study used Descriptive Analysis, Reliability Analysis, Correlation Analysis, and Multiple Regression Analysis to prove the relationship between the three independent variables and dependent variable. Meanwhile, the data analysis was conducted using Statistics Packages for Social Science (SPSS) software version 24. Based on the results, it shows that all the independent variables which are brand image, price and social influence have significant relationship on the purchase intention towards counterfeit products.